Researching the Influence of the Kinds and Content of Carbohydrate on the Mycelial Growth and Polysaccharides Production of Ganoderma lucidum in Submerged Culture - Nguyen, Phan Khanh Hoa; Le, Thi Thuy Tien; Nguyen, Duc Luong (Old Journal, 2018)
This investigation was conducted to determine the role of carbohydrate in submerged Ganoderma lucidum DL and Ganoderma lucidm TP (isolated in Vietnam). The results showed that for DL strain, biomass, EPS and IPS were highest when using lactose 60 g/l; whereas, 60 g/l sucrose is suitable for biomass, IPS, EPS of TP strain. Under the conditions of submerged fermentation with suitable carbohydrates, the biomass of TP strain was higher than the DL strain (14.091 ± 1.174, 13.470 ± 0.073 g dry weight/l, corresponding to TP and DL strain), but the amount of PS obtained in DL strain werw higher than in TP. The IPS and EPS content obtained in DL strain was 10.23 ± 0.10 mg/100 mg dry weight and 1347.83 ± 38.54 mg/l, TP strain was 12.64 ± 0.33 mg/100 mg dry weight và 12.64 ± 0.33 mg/l.